Pretreatment of Terrestrial Macrofossils. Issue 2 (27th April 2020) - Norris, Margaret W; Turnbull, Jocelyn C; Howarth, Jamie D; Vandergoes, Marcus J
ABSTRACT: Acid-alkali-acid (AAA) pretreatment is widely used to clean terrestrial plant macrofossil samples for radiocarbon ( 14 C) dating. There is wide variation amongst laboratories in the AAA method details and less rigorous AAA pretreatment is often used on fragile or small samples. Yet there is little evidence as to the efficacy of the different methods and whether the use of less rigorous methods is justified. We investigated four variations of AAA pretreatment: acid only (no alkali wash); room temperature AAA; "standard" AAA at 85°C; and "aggressive" AAA at 85°C with alkali washes repeated until no discoloration was detected. We tested six different terrestrial macrofossils from four different locations and ranging in age from mid-Holocene to the Last Glacial Maximum. Our results demonstrate that while acid only is not always sufficient to remove young material, there is no difference in 14 C age of samples pretreated by any of the AAA variants. We also observed mass loss of 85–90% in the standard and aggressive AAA pretreatments, and much more modest mass loss in the room temperature AAA pretreatment. Therefore, we conclude that room temperature AAA pretreatment is optimal to remove contaminating material from fragile terrestrial macrofossils while retaining the majority of the authentic sample material.